2010
DOI: 10.1038/jp.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

The changing spectrum of neonatal infectious disease

Abstract: To understand the changing spectrum of neonatal infectious disease, one must first be familiar with the history, the variety of organisms and the progression of change of neonatal infections over the years. As progressively more immature neonates are surviving, the spectrum of infectious disease has changed in response to current medical practice responsible for this success and to selective pressures on the microorganisms. The surviving very low birth weight infants are at a significant risk for contracting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
2
12
0
2
Order By: Relevance
“…Our study confirmed these risk factors for development of EOS. As expected, vaginal delivery is significantly more frequent in our septic group infants because of the exposure of infants to microorganisms in birth canal (Plano 2010 most commonly isolated pathogens in positive blood cultures of our septic infants, and those findings are in concordance with previous studies (Plano 2010;Cortese et al 2016). TNF-α and IL-6 are primary proinflammatory cytokines that mediate the initial response of the innate immune system to infection and have an important role in the pathogenesis of sepsis.…”
Section: Discussionsupporting
confidence: 93%
“…Our study confirmed these risk factors for development of EOS. As expected, vaginal delivery is significantly more frequent in our septic group infants because of the exposure of infants to microorganisms in birth canal (Plano 2010 most commonly isolated pathogens in positive blood cultures of our septic infants, and those findings are in concordance with previous studies (Plano 2010;Cortese et al 2016). TNF-α and IL-6 are primary proinflammatory cytokines that mediate the initial response of the innate immune system to infection and have an important role in the pathogenesis of sepsis.…”
Section: Discussionsupporting
confidence: 93%
“…Birthweight and gestational age have been shown in the literature to be the predominant patient related risk factors for healthcare-associated infections [2,19-21]. We could fully confirm these findings our study.…”
Section: Discussionsupporting
confidence: 84%
“…Neonates (babies in their first 28 days of life) and infants (first year of life) have a premature immune system and are a particularly vulnerable population for infectious diseases and hence resistant bacteria [8,11,17–19]. In LMIC, neonatal infection rates are 3 to 20 times higher than in high-income countries (HIC) and 40% of neonatal deaths are attributable to infectious diseases in general [11,20,21].…”
Section: Introductionmentioning
confidence: 99%